EVALUATING THE IMPACT OF A MULTIMODAL EDUCATION PROGRAM TO IMPROVE NURSING ASSISTANTS’ SKILLS IN DELIRIUM SCREENING AND MANAGEMENT: A PRE-POST STUDY - Khaled Saud Dahi Alfadhli 1, Faisal Brahim Hlyel Alshammari 2, Sami Saud Dahi Alfadhli 3, Fahad Brahim Hilyal Alshammari 4, Abdulaziz Sulaiman Awadh Alharbi 5, Haya Muhaisen Hlyel Alshammari 6 (Chelonian Research Foundation, 2022)
Delirium is common yet underdetected in hospitalized patients, compromising outcomes. Nursing assistants play a crucial role in routine observation and screening to facilitate early delirium identification and management. This study evaluated impacts of a multimodal delirium education program on nursing assistants’ knowledge, attitudes, and screening skills at a tertiary hospital in Saudi Arabia. Fifty assistants completed interactive workshops, simulation scenarios, and competency assessments before and after training. Knowledge test scores significantly improved from a mean of 55% to 88% post-training. Qualitative feedback emphasized enhanced delirium awareness, confidence, and therapeutic communication preparation. Screening competency including observations, tool administration, interpretation, and reporting steps increased from a baseline mean of 2.9 to 4.7 on a 5-point scale after training. Multifaceted education effectively boosted assistants’ delirium capabilities, with implications for broader implementation and practice changes to improve detection and team collaboration. Keywords: delirium, nursing assistants, education, skills, competency, pre-post study